REHABILITATION TECHNIQUES OF MASSAGE AND TAPING IN FOOTBALL - Horoshko, V. I.; Moskalets, V. O.; Soloviov, Ye. (Rehabilitation and Recreation, 2022)
The relevance of the work is determined by the need to improve restorative rehabilitation methods in youth sports. The purpose of this study is to study the impact of the use of health-preserving technologies by school-aged football players on the prevention of injuries and illnesses during competitive activities and/or games for the further development of preventive measures taking into account an individual approach. The object of the study: injuries in football among athletes aged 14-16 years. The subject of the research: author's technique of restorative massage for young football players and evaluation of the effectiveness of the restorative measures on physical performance, preventive taping. The task of the research: to evaluate the effectiveness of the developed massage techniques; to study the physical characteristics of young football players before and after rehabilitation measures; to develop and test their own methods of massage and preventive taping for football players aged 14-16. The following methods were used in the work: statistical, economic, experimental, sociological, analysis of scientific and methodological literature, control, and pedagogical tests. Conclusions: 1. Studies of the localization of injuries show that about 80% of football injuries are related to the lower limbs (knee joint, about 40%). 2. The analysis of the dynamics of indicators of special physical fitness showed that the increase in sports injuries among football players aged 14-16 was average, and that of speed and strength qualities was above average. The general level of special health is above average. 3. Identified injury risk factors help to eliminate defects and reduce the level of injuries with the help of modern massage and taping techniques. The technique is effective in the recovery of athletes, is easy to use, does not require a lot of time, and can be successfully used by sports doctors.